Signifikansi Dakwah Multikultural Ulama Perempuan dalam Proses Pemberdayaan Masyarakat: Studi Kasus pada Aktivitas Dakwah Jam’iyah Muslimat NU Cabang Jember: The Significance of Multicultural Da'wah by Female Ulama in the Community Empowerment Process: A Case Study on the Da'wah Activities of the Jam’iyah Muslimat NU Jember - Hepni, Hepni (LP2M UIN KH.Achmad Siddiq Jember, 2008)
-